Do government environmental audits reduce air pollution? Evidence obtained from Lanzhou - Chen, Tianyou; Li, Ji (Frontiers in Public Health, 2024)
This study adopts a regression discontinuity design to empirically evaluate the impact of the pilot government environmental audit project conducted by the former Ministry of Environmental Protection on the prevention of air pollution in Lanzhou City. Our findings reveal a notable decline in the Air Quality Index (AQI), from 31 to 25, during and subsequent to the implementation of these audits. To ensure the robustness of our analysis, we conducted extensive testing on the AQI and optimal bandwidths of six key pollutants, determined via mserd calculation. For each explanatory variable, adjustments to the optimal bandwidth by -20% and +40% were made to evaluate sensitivity. Precipitation levels also increased significantly by 0.241% post-audit, indicating potential environmental improvements. The reliability of the regression results is further confirmed by robustness tests that include adjusting the bandwidth, testing the continuity of control variables, and eliminating control variables. The research outcomes verify the administrative effects of the government environmental audit: it effectively decreases air pollution by supervising local governments in the implementation of environmental protection policies.